Peculiarities of Information Competence of a Teacher in the Context of Countering Negative Informational and Psychological Influence on Future Officers in the Process of Training During Hybrid Warfare - Halus, Oleksandr; Polishchuk, Oleksandr; Zdanevych, Larysa (Pedagogical Discourse, 2024)
The article analyzes the peculiarities of information competence of a teacher in the context of countering negative informational and psychological influence on future officers in the process of training during hybrid warfare. The definition of measures to counteract destructive information and information-psychological influence in the context of hybrid confrontation is clarified. The mechanisms and means of propaganda influence on the personality are clarified. It is emphasized that in order to effectively combat hostile disinformation at the national level, it is necessary to consolidate the efforts of the conscious part of society. This category includes professionals who have direct contact with people, including teachers, psychologists, media representatives, content makers, religious leaders, librarians, and representatives of public and cultural organizations. A significant role in this confrontation is played by professors of higher military educational institutions who teach future officers. The effectiveness of their activities directly depends on the level of information and psychological competence, ability to defend Ukrainian values, awareness of the real state of affairs, understanding the scale of threats and the ability to effectively counter them. Prevention of information diffusion is a set of measures aimed at protecting the information space of a country, organization or community from external influence, manipulation and disinformation. The main areas of information protection are: compliance with legal regulations; strengthening cybersecurity; sufficient media literacy and developed critical thinking of the population; development of its own information space; international cooperation. The author identifies the main components of an officer’s information literacy: media literacy; the need for information retrieval and analysis; the development of critical thinking and fact checking; effective use of digital technologies; digital literacy; communication skills and information transfer; ethical and legal aspects.